Longitudinal growth in college student self-efficacy and intercultural competence attenuated by anxiety/depression - Peifer, Janelle; Taasoobshirazi, Gita; Meyer-Lee, Elaine (Frontiers in Education, 2023)
A wide range of stakeholders, including prospective students, parents, accreditors, future employers, and the general public, require detailed data on college outcomes. However, there are many challenges to producing such complex research tracking change over time in the higher education setting. This multi-method longitudinal study at three different colleges was grounded in Input-Environment-Output and Social Cognitive theoretical frameworks. It examined: potential change on five different key psychosocial outcomes (i.e., self-efficacy, anxiety, intercultural competence, ethnic identity, and cognitive empathy), associations between these variables, and the role of race/ethnicity. Multilevel growth modeling revealed within and between subject changes over time. The findings provide evidence that liberal arts colleges focused on global learning can produce significant growth for students of all races on self-efficacy and intercultural competence, both outcomes that are valued for workforce readiness. However, the results also show that anxiety and depression symptoms attenuate growth in intercultural competence, which is concerning given other recent data on students' mental health and wellness concerns. We discuss implications for student development practitioners and faculty alongside potential future directions for research in other higher education settings.